ARAH BARU KAJIAN TAFSIR: (Kajian Metodologi Penelitian Aksin Wijaya dalam Karyanya Sejarah Kenabian Perspektif Tafsir Nuzuli Muhammad Izzat Darwazah) - Cholid Ma'arif (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
This paper will explore aspects of research methodology of exegesis written by Aksin Wijaya related to methods nuzuli ala Muhammad Izzat Darwazah. For that, the focus of this discussion is the methodology of his research in his own book of under title Sejarah Kenabian Dalam Perspektif Tafsir Nuzuli Muhammad Izzat Darwazah, finding out how people review mufassir. Specifically, the methodical determination of the previous his experienced has moved soon of orientation from the critical to the descriptive while facing of four books, namely: Tafsir al Hadith, 'Ashr al Nabiy wa Biatuhu Qabla al Bi'tsah, Sirah al Rasul; Suwar Muqtabasah min al Qur'an, and ad Dustur al Qur'an fi Su'uni al Hayat works of thinkers and historians. From his reading, he at least analyzes his views into two important parts, namely; 1) the interpretation method of nuzuli and the ideal concept it contains, 2) it then draws it into the realm of pre-Islamic, personal and family life of the prophet Muhammad, to the condition of the people of prophetic era through the perspective of nuzuli Izzat Darwazah exegesis. According to the reviewer, there are other research elements in writing the work of the exegesis, namely some models of research methods of interpretation at once, such as: comparative research, character research, and thematic-nuzuli research. Whereas although placed more as an overview of nuzuli interpretation, at least he invites readers, especially in Indonesia to re-read the tafsir nuzuli treasury and see which is as worthy to be developed in the turats of Islam Nusantara.